2022
DOI: 10.1093/aobpla/plac024
|View full text |Cite
|
Sign up to set email alerts
|

Differential tolerance to heat stress of young leaves compared to mature leaves of whole plants relate to differential transcriptomes involved in metabolic adaptations to stress

Abstract: Plants respond to heat shock by regulating gene expression. While transcriptomic changes in response to heat stress are well studied, it is not known whether young and old leaves reprogram transcription differently upon stress. When whole plants of Arabidopsis thaliana were subjected to heat shock, young leaves were affected significantly less than older leaves based on measurements of tissue damage. To identify quantitative changes to transcriptomes between young and old leaves upon heat stress, we used RNA-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…A study comparing leaves of the same age in 1 (pre-reproductive), 3 (transition phase) and 7-year-old (mature non-senescing) plants of the evergreen halfshrub Cistus clusii Dunal reported enhanced formation of malondialdehyde in leaves and chloroplasts, decreased photosynthetic activity, lower chlorophyll and antioxidant levels in the chloroplast in 7-years old plants compared to 1-and 3-years old plants (Munné-Bosch and Alegre 2002). Moreover,Xiang and Rathinasabapathi (2022) found that in Arabidopsis, older leaves accumulated three times more H 2 O 2 compared to young leaves in both control and heat-stressed conditions. Another plausible explanation is that increased cellular respiration in surviving plants may have depleted sugar and carbohydrate reserves, resulting in either loss of energy homeostasis, eventually leading to death or inhibited ability to recover and re-establish after freezing stress.…”
mentioning
confidence: 95%
“…A study comparing leaves of the same age in 1 (pre-reproductive), 3 (transition phase) and 7-year-old (mature non-senescing) plants of the evergreen halfshrub Cistus clusii Dunal reported enhanced formation of malondialdehyde in leaves and chloroplasts, decreased photosynthetic activity, lower chlorophyll and antioxidant levels in the chloroplast in 7-years old plants compared to 1-and 3-years old plants (Munné-Bosch and Alegre 2002). Moreover,Xiang and Rathinasabapathi (2022) found that in Arabidopsis, older leaves accumulated three times more H 2 O 2 compared to young leaves in both control and heat-stressed conditions. Another plausible explanation is that increased cellular respiration in surviving plants may have depleted sugar and carbohydrate reserves, resulting in either loss of energy homeostasis, eventually leading to death or inhibited ability to recover and re-establish after freezing stress.…”
mentioning
confidence: 95%
“…This indicates that the elevated glycolytic rate in field survivors compared to the original material may have depleted carbohydrate reserves while also leading to increased accumulation of anaerobic byproducts. Previous studies in Arabidopsis thaliana and Cistus clusii showed that older plants and leaves accumulated more H 2 O 2 and malondialdehyde (Munné-Bosch and Alegre, 2002; Xiang and Rathinasabapathi, 2022) indicating higher oxidative stress in ageing plants and tissues. Thus, the elevated expression of glutathione s-transferase, catalase, aldehyde oxidase, aldo-keto reductase, short-chain dehydrogenase/reductase linked to ROS scavenging and detoxification (Simpson et al, 2009; Mhamdi et al, 2010; Vijayakumar et al, 2016; Wu et al, 2022b) in field survivors compared to the original material might be due to a combination of selection in the field and the age effect.…”
Section: Discussionmentioning
confidence: 96%
“…The highest enrichment app the gmx00040 (pentose and glucuronate interconversions) of 25 genes in the flo root. The pentose and glucuronate interconversions pathway had been reported involved in male sterility in cotton [53], stress [54], and pathogen infection ada [55] in Arabidopsis and woody plants, respectively. The enrichment of significant GO terms (p-value < 0.05) and their descriptions was obtained from Phytozome with a reference Williams 82 genome.…”
Section: Go and Kegg Enrichment Analysis Of Tissue-specific Genesmentioning
confidence: 99%